Impairment of inhibitory control in response to food-associated cues and attentional bias of obese participants and normal-weight controls - Steins-Löber, Sabine; Großhans, Martin; Korucuoglu, Ozlem; Vollmert, Christian; Vollstädt-Klein, Sabine; Schneider, Sven; Wiers, Reinout; Mann, Karl; Kiefer, Falk (International journal of obesity, 2012)
Objective: Starting from a model of impaired response inhibition and salience attribution for addictive behaviour we investigated whether obese participants show a greater impairment of inhibitory control in response to food-associated cues compared with neutral stimuli and whether this is seen in normal-weight control subjects. In addition, we questioned whether an attentional bias towards food-associated cues can be observed in an early stage of information processing. Design: Control-group study including the administration of behavioural tasks (that is, go/no-go task with food-associated and neutral words, visual dot probe task with food-associated and neutral pictures) and self-reported measures of eating behaviour and impulsivity. Results: Although self-reported measures indicated disinhibition of eating behaviour of obese patients, we found that food-associated stimuli induced an impairment of inhibitory control in both obese participants as well as normal-weight controls. Results from the visual dot-probe task indicated that food-associated cues did not modulate attention allocation in a very early stage of information processing, which suggests that the incentive salience of food-associated stimuli might be lower than that of drug-associated cues. Conclusion: These findings are not in line with hypotheses derived from models of addictive behaviour and call into question that an impairment of inhibitory control in response to food-associated cues and salience attribution might be at the core of obesity. Future studies using larger sample sizes and refined experimental procedures are warranted to further investigate mechanisms controlling food intake in obesity.